Subgenera of the genus Pentamerismus McGregor (Acari: Tenuipalpidae) with the re-description of Pentamerismus retusus Meyer and a key to species of the world - Mirza, Jawwad Hassan; Elgoni, Nasreldeen Ahmed; Kamran, Muhammad; Alatawi, Fahad Jaber (Zootaxa, 2025)
After critically assessing of the published literature for all 23 species of the tenuipalpid genus Pentamerimus McGregor, 1949, this taxon is divided into two subgenera: subgenus Pentamerismus McGregor, 1949 with setae f2 present (12 species) and a restored subgenus Oligomerismus Mitrofanov, 1973 lacking setae f2 (11 species). Based on the material from Saudi Arabia, the male of Pentamerismus (Oligomerismus) retusus Meyer, 1979 is for the first time described, and the complementary description of the female is provided. The generic affiliation of P. (O.) collinus Meyer & Van Dis, 1993 is discussed. Additionally, an updated key to all known species of the genus Pentamerismus is provided.